Dispute Resolution Practices in Private and Public Banks of Nepal: A Comparative Study - Neupane, Shova (Nepalese Journal of Development and Rural Studies, 2024)
Effective dispute resolution is integral to maintaining customer trust and operational stability in banking, particularly in developing economies. This study comparatively examines dispute resolution practices in Nepal’s private and public commercial banks. The specific objectives are to identify predominant dispute types, assess the mechanisms employed to resolve them, evaluate their effectiveness, and explore how governance structures influence resolution strategies. Employing a convergent parallel mixed‑methods design, we surveyed 210 participants (customers and bank staff) from one private bank (Global IME Bank) and one public bank (Nepal Bank Ltd.) and conducted semi‑structured interviews and focus groups. Quantitative data were analyzed via descriptive and inferential statistics (χ² and t‑tests), while qualitative data underwent thematic analysis. This research identified transaction errors, interest and fee discrepancies, and service delivery issues as the most common disputes. Internal resolution methods, particularly negotiation and grievance redressal systems, remain primary but show varying degrees of effectiveness and customer satisfaction.